Phenomenology of Teachers’ Administrative Task Removal - Testa, Ma. Sheila A.; Delavin, Elreen A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study employs a qualitative research design to explore the lived experiences of teachers regarding the removal of administrative tasks as mandated by DepEd Order No. 002, s. 2024. It aims to gain an in-depth understanding of how this policy shift influenced teachers’ instructional practices, professional development, student learning outcomes, well-being, and job satisfaction. Using a phenomenological approach, the study conducted semi-structured interviews with ten public school teachers from the Mandaon South District to capture their narratives and personal insights. The data gathered were analyzed through Braun and Clarke’s (2006) six-phase thematic analysis, which enabled the identification of recurring patterns and themes reflective of the participants' experiences. The findings revealed that while the removal of administrative duties enhanced instructional quality, teacher focus, and work-life balance, these benefits varied due to inconsistencies in implementation. Challenges such as unclear role boundaries, insufficient institutional support, and lingering workload stress were also noted. Teachers emphasized the importance of strategic staffing, sustained professional development, and access to learner-centered resources to maximize the policy's intended impact. Overall, the study highlights the transformative potential of administrative relief when coupled with consistent execution and robust support systems. The results provide valuable implications for education policymakers and school leaders striving to improve teacher effectiveness and well-being.